Sistem Penunjang Keputusan Untuk Menentukan Penerima Beasiswa Berdasarkan Metode MULTI-KRITERIA (SAW, WP, TOPSIS) - Mashun Yusuf; Muhamad Fikri Romadhon; Putra Dwi Septian; Eka Jurnaditllah; Moh Fiqih Nurhidayatullah; Putra Ardiyansyah Koeswara; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Scholarship distribution is a form of support to enhance educational access, particularly for high achieving students from underprivileged families. However, manual and subjective selection processes often lead to unfairness and inefficiency. This study aims to design and develop a decision support system based on multi-criteria methods, namely Simple Additive Weighting (SAW), Weighted Product (WP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), to assist in an objective and measurable scholarship selection process. The system was developed using the Waterfall model approach and tested using candidate data based on predefined criteria. Implementation results show that all three methods produce consistent rankings, with Alternative 2 consistently emerging as the best choice. The system provides accurate and fast calculations, supported by a user-friendly interface. The application of these multi-criteria methods enhances transparency, objectivity, and accountability in the scholarship selection process.